Polymerization kinetics and polymerization stress in resin composites after accelerated aging as a function of the expiration date - D'Alpino, Paulo Henrique Perlatti; Svizero, Nádia da Rocha; Arrais, César Augusto Galvão; Oliveira, Michele de; Alonso, Roberta Caroline Bruschi; Graeff, Carlos Frederico de Oliveira [UNESP] (Elsevier B. V., 2015)
To determine the effect of material condition (new, aged, and expired) on the polymerization kinetics and polymerization stress of different classifications of dental composites. Specimens were obtained according to the following factors: Composites: (3M ESPE) Filtek P60, Filtek Z250, Filtek Z350XT, and Filtek Silorane; and Material conditions: new, aged, and expired. The syringe composites underwent an accelerated aging protocol (Arrhenius model) representing approximately 9 months of aging. Infrared (IR) spectra were obtained kinetically and were analyzed for: maximum conversion rate (%/s), time into exposure when maximum rate occurred (s), conversion at maximum rate (%), and total conversion (%) at 90 s by comparison of absorption IR peak ratios before and after polymerization. Polymerization was evaluated at the bottom surface of 2.0 mm-thick specimens. Polymerization stress was determined in a tensilometer, inserting the composite between acrylic rods fixed to clamps in a universal test machine and dividing the maximum load recorded by the rods cross-sectional area. Polymerization stress (MPa) was calculated at 300 s. Data were statistically analyzed by two-way ANOVA and Tukey's post hoc test (α=0.05). The majority of the polymerization kinetic parameters were not influenced by the material condition. Silorane composite presented significantly lower conversion rate and lower conversion at the maximum rate when expired (p<0.05). The nanofilled composite (Filtek Z350XT) presented a significantly higher total conversion when aged and expired compared to the new one (p>0.05). In all conditions, Filtek Z350XT and Filtek Silorane presented significantly lower conversion rates (p < 0.05). Filtek Silorane also exhibited the lowest stress, irrespective of the material condition (p<0.05). The polymerization stress was not influenced by the material condition (p>0.05). Most of the kinetic parameters are not influenced by the material condition. Filtek P60 and Filtek Z250 are more stable as both composites present similar polymerization kinetic results, irrespective of the material condition. Silorane composite presents lower stress values among the tested materials in all conditions. Aging does not affect stress development in restorative composites.
Keywords: Aging; Composite resins; Contraction stress; Methacrylate; Monomer conversion; Silorane